Tradisi lisan sebagai bahan pengembangan materi ajarPendidikan IPS di SMP: sebuah telaah literatur - Syaputra, Een; Dewi, Desy Eka Citra (Jurnal Teori dan Praksis Pembelajaran IPS, 2020)
In addition to models, methods, and media, another aspect that is also very important in social studies is teaching material. As an essential element in the learning process, teaching materials must have adequate quality. Accordingly, this article is intended to offer a literature overview of oral traditions as material development for social studies in junior high schools, as well as to design conceptual models related to their application. This article is a conceptual article compiled based on the results of literature studies (books, journals, etc.) and document analysis (Core Competencies, Basic Competencies, Syllabus, etc.). There are three findings offered by this article. First, oral tradition is a potential source to be developed into social studies in junior high schools as it contains values of local wisdom and moral teachings which are relevant to the vision of social studies, namely as civic education. Also, oral traditions, which are part of anthropology and history, share the same nature to social study materials-combination of social science disciplines. Second, from several oral tradition variants, the most potent type to be inserted in social study materials are traditional expressions, folk poetry, folklore, and folk songs-by considering three things, namely: a) curriculum relevance; b) richness in value content; c) school environment-related issues. Third, three stages can be done in developing oral traditions as teaching materials, namely: a) analysis stage (identification of oral tradition and its relevance to curriculum); b) design and development stage (determining the form and structure of teaching materials required); and c) implementation stage.DOI: 10.17977/um022v5i12020p051